SYNTHESIS, CHARACTERIZATION, AND ANTIMICROBIAL EVALUATION OF NEW N-PHENYLCINNAMAMIDE DERIVATIVES LINKED TO ASPIRIN AND IBUPROFEN - Alwash, Ameer H; Mahdi, Alaa M; Al-karagully, Haider J (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to synthesize phenylcinnamamide (substituted acetanilide chalcone) derivatives linked to aspirin and ibuprofen with potential antibacterial and antifungal activity. Methods: Substituted acetanilide compounds were reacted with different arylaldehydes through Claisen-Schmidt condensation in the presence of KOH. They formed differently substituted acetanilide chalcones (1a-e) which are linked to aspirin and ibuprofen through an ester linkage to form compounds (2a-j) using ethyl chloroformate (ECF) as a catalyst. Results: The synthesized compounds have been characterized by elemental analysis, Fourier transform infrared and1H-nuclear magnetic resonance spectroscopy. An antibacterial evaluation was achieved for Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) and antifungal for Candida albicans. Conclusion: Compounds (2a-j) have shown intermediate antimicrobial activity against different strains of microorganisms.